Intercultural Effectiveness of International and Domestic University Students: A Case of Turkey - Avcılar, Ahsen; Gök, Enes (Journal of International Students, 2021)
Among the vast and diverse discussions and research on international students, the intercultural status of university students holds a special place in terms of integration and academic success. One of the discussions is the intercultural competencies of the students in higher education. In this respect, this study aims to compare the intercultural effectiveness of international and domestic students, as well as examine their intercultural effectiveness status in terms of different background characteristics. The data were collected from a public university in Turkey using the Intercultural Effectiveness Scale developed by Portalla and Chen. The findings revealed that international students compared with domestic counterparts show a higher level of intercultural effectiveness. Additionally, some background characteristics are significant predictors of the intercultural effectiveness of university students: grade level, parent’s nationality, being and living in a foreign country, and having a close friend(s) from a different culture. Some research and policy recommendations are provided.